INTENSITAS KEBAKARAN LAHAN GAMBUT BERDAMPAK PADA KEMASAMAN TANAH DI KEBUN KELAPA SAWIT, KABUPATEN TULANG BAWANG, PROVINSI LAMPUNG - Ghani Ilham Prawiradijaya; Syahrul Kurniawan (Jurnal Tanah dan Sumberdaya Lahan, 2021)
Peatlands have specific characteristics, namely irreversible drying, so that become flammable. Peat fires have an impact on changes in soil pH. The study aimed to analyze the soil acidity after peatland fires in oil palm plantation. This study used a survey method on two main plots (low and high fire intensity). Samples were taken at two soil depth including 0-10 cm and 11-30 cm in three zones (fertilization area, harvest path and frond pile zone) and repeated three times. Data were analyzed by ANOVA using the 5% nested test, then LSD test, and analyzed for correlation. The results showed that the soil pH on all land was included in the very acid category. Soil pH in the land B (land with high fire intensity) is higher than those in the land A (land with low fire intensity), both in top soil and sub soil. The micro-nutrient elements of Fe and Al in the land B are lower than land A, while the micro-nutrients of Mn in land B are higher than land A. The correlation of soil pH towards Fe and Al is negative, while for Mn is positive (pH increases, acid cations of Fe and Al will decrease while acid cations of Mn will increase). This was presumably due to competition in occupying the land-catchment complex.